PEMBUKTIAN DALAM PERKARA TINDAK PIDANA NARKOTIKA (STUDI PUTUSAN NOMOR 98/Pid.Sus/2021/PN.Tab): Evidence In Narcotics Criminal Cases (Study Decision Number 98/Pid.Sus/2021/PN.Tab) - Syakia Brafnasha Isabella Pambudi; Setiyono (AMICUS CURIAE, 2025)
Law Number 35 of 2009 on Narcotics stipulates that abusers of narcotics category I for personal use shall be sentenced under Article 127 paragraph (1). However, in Decision 98/Pid.sus/2021/PN.Tab, the Panel of Judges imposed a sentence on a narcotics abuser for personal use under Article 112, which applies to intermediaries and dealers. This study identifies problems concerning whether the Panel of Judges’ legal considerations, which disregarded the consistency of evidence presented in court, were accurate and in accordance with the prevailing laws, as well as the evidentiary strength in Tabanan District Court Decision Number 98/Pid.sus/2021/PN.Tab. The research type is normative legal research using secondary data with a descriptive-analytical nature. The data were processed qualitatively, and conclusions were drawn deductively. With the results of the research and conclusion, it was found that the Panel of Judges’ reasoning, which failed to carefully examine the consistency of the evidence, did not align with the objectives of evidentiary law, rendering the decision inaccurate and inconsistent with existing regulations. Meanwhile, the evidentiary strength in the case was valid under Article 184 of the Criminal Procedure Code, proving that the defendant purchased narcotics for personal use and not for distribution.